2013
DOI: 10.1371/journal.pone.0070505
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Rapidly Increases GABA Release in the Dorsal Motor Nucleus of the Vagus via Retrograde Messenger-Mediated Enhancement of TRPV1 Activity

Abstract: Glucocorticoids influence vagal parasympathetic output to the viscera via mechanisms that include modulation of neural circuitry in the dorsal vagal complex, a principal autonomic regulatory center. Glucocorticoids can modulate synaptic neurotransmitter release elsewhere in the brain by inducing release of retrograde signalling molecules. We tested the hypothesis that the glucocorticoid agonist dexamethasone (DEX) modulates GABA release in the rat dorsal motor nucleus of the vagus (DMV). Whole-cell patch-clamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 49 publications
2
7
0
Order By: Relevance
“…This is consistent with previous findings indicating that the TRPV1 agonist, capsaicin increases the release of glutamate, which binds preNMDAR and enhances GABA release in DMV neurons (Derbenev et al, 2006, Derbenev and Smith, 2013). Similarly, blockade of AMPA/KA receptors with CNQX, but not selective AMPAR blockade with GYKI-52466, suppressed the capsaicin-induced increase in mIPSC frequency.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This is consistent with previous findings indicating that the TRPV1 agonist, capsaicin increases the release of glutamate, which binds preNMDAR and enhances GABA release in DMV neurons (Derbenev et al, 2006, Derbenev and Smith, 2013). Similarly, blockade of AMPA/KA receptors with CNQX, but not selective AMPAR blockade with GYKI-52466, suppressed the capsaicin-induced increase in mIPSC frequency.…”
Section: Discussionsupporting
confidence: 93%
“…Previous experiments in rats and mice indicated that TRPV1 activation with capsaicin enhanced mIPSC frequency in the DMV, and that a significant proportion of this effect was due to TRPV1-mediated release of glutamate, which binds iGluRs located on the synaptic terminals of afferent GABAergic neurons (Derbenev et al, 2006, Derbenev and Smith, 2013). To establish that glutamate could act at presynaptic terminal receptors to increase GABA release in the mouse DMV, we determined the effect on mIPSCs of L-glutamate (50 μM) in nine DMV neurons, voltage-clamped at 0 mV to reduce direct effects of the agonist on the recorded neuronal membrane.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Glutamate GABA imbalance has been implicated in anxiety disorders and the response seen here could be the result of dexamethasone eliciting an increase in brain glutamate levels enough to alter the glutamate GABA balance. Increases in glutamate efflux in brain regions such as the prefrontal cortex and hippocampus was observed after stress; also a lack of GAD65 enzyme which is responsible for converting glutamate into GABA leads to exhibition of anxiety in mice [21] [22]. Actions of corticosteroids in the limbic region of the brain are strongly linked to their observed anxiogenic response and a disruption of their forebrain/limbic circuits is probably involved in the development of affective and anxiety disorders [23].…”
Section: Discussionmentioning
confidence: 99%